Theory of potential impurity scattering in pressurized superconducting La3Ni2O7 - Steffen Bötzel; Frank Lechermann; Takasada Shibauchi; Ilya M. Eremin (Communications Physics)
Abstract Recently discovered high-T c superconductivity in pressurized bilayer nickelate La3Ni2O7(La-327)is likely driven by the non-phononic repulsive interaction. Depending on the interlayer repulsion strength, the superconducting gap structure is expected to be either d-wave or sign-changing bonding-antibonding s ±-wave. Unfortunately, conventional spectroscopic probes of the gap structure are impractical due to the high-pressure requirement. We propose studying the effect of point-like non-magnetic impurities to distinguish these symmetries, which can be achieved by electron irradiation before applying pressure. Here, we theoretically predict conventional suppression for d-wave superconductivity, whereas the suppression for the interlayer s ± -wave state depends subtly on the asymmetry of bonding and antibonding subspaces. For the predicted electronic structure of La-327, the s ± -wave is more robust, with T c showing a convex-to-concave transition, indicating a crossover to s ++-wave symmetry as impurity concentration increases. We further analyze the sensitivity of these findings to potential electronic structure modifications.